Experimental Study On The Mechanical Properties Of Eco-Friendly Concrete - Ahmad Fauzi; Budi Santoso; Rina Puspita (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
This paper investigates the mechanical properties of eco-friendly concrete incorporating recycled aggregates and industrial by-products. An experimental program was conducted to assess the compressive strength, tensile strength, and durability of various concrete mixes. The results reveal that the use of recycled materials can produce concrete with comparable mechanical properties to conventional concrete. This study highlights the potential of eco-friendly concrete in reducing environmental impacts while maintaining structural integrity.